Juego de roles y el lenguaje oral en los niños del nivel inicial II de la Unidad Educativa José Ángel Palacio de la ciudad de Loja, periodo 2021 – 2022. - Sarango Ruiz, Yessenia Maricel (2023)
Oral language is one of the essential areas of the human being, due to the fact that it allows transferring ideas, thoughts, feelings among others, being fundamental its stimulation in the first years of life; therefore, in the present research it was proposed as an objective to determine how role-playing games improve oral language in children of the initial level II of the José Ángel Palacio Educational Unit of the city of Loja, period 2021-2022; for this, a quasi-experimental research was conducted, with a mixed approach, with the help of methods such as: inductive - deductive that allowed to collect specific data of the research to establish general conclusions and the analytical - synthetic that contributed in the collection of the necessary information of the variables and study them individually. The instrument used was the PLON-R Test (Oral Language Test of Navarra - Revised), applied to a sample of 12 children of the initial level II, it was used as a pre-test obtaining as a result that 83% of the children were in a level of delay and need of improvement in the development of language and 17% in a normal level, Based on these needs, an activity guide based on role playing was designed and applied to improve the children's oral language. Finally, the post-test showed that 92% of the children presented normal language development and 8% presented a delay in language development, concluding that role playing favors the resources to develop oral language through representations. Key words: language, roles, children, play, activities.